Blockade of Extracellular HMGB1 Suppresses Xenoreactive B Cell Responses and Delays Acute Vascular Xenogeneic Rejection. Issue 8 (5th May 2015) - Li, J.‐H.; Zhao, B.; Zhu, X.‐H.; Wang, L.; Zou, H.‐J.; Chen, S.; Guo, H.; Ruan, Y.‐L.; Zheng, F.; Xiang, Y.; Ming, C.‐S.; Gong, F.‐L.; et al.
<x xml:space="preserve">Abstract</x> Blockade of extracellular high mobility group box 1 (HMGB1) can significantly prolong murine cardiac allograft survival. Here, we determined the role of HMGB1 in xenotransplantation. Sprague‐Dawley rat hearts were transplanted heterotopically into BALB/c mice. Xenografts without any treatment developed predominant acute vascular rejection within 6 days. Both passively released HMGB1 from xenografts and actively secreted HMGB1 from infiltrated immune cells were significantly increased after xenotransplantation. HMGB1‐neutralizing antibody treatment significantly prolonged xenograft survival and attenuated pathologic damage, immune cell infiltration, and HMGB1 expression and release in the xenografts. Compared to control IgG treatment evaluated at study endpoint, treatment with HMGB1‐neutralizing antibody markedly suppressed xenoreactive B cell responses, as evidenced by the significant inhibition of anti‐rat antibody production and deposition in xenografts at Day 6 posttransplant. Furthermore, treatment with anti‐HMGB1 antibody suppressed B cell activation and reduced IFN‐γ and IL‐17A production after xenotransplantation. These results demonstrate for the first time that HMGB1 plays an important role in mediating acute xenograft rejection. Thus, we have shown that neutralization of extracellular HMGB1 can significantly inhibit xenoreactive B cell responses and delay xenograft rejection in a rat‐to‐mouse model of xenotransplantation, uncovering new insights in the role of HMGB1 in transplantation.